TINGKAT STRES MAHASISWA DALAM PEMBELAJARAN ONLINE PADA MASA PANDEMI COVID-19 - Meilla Dwi Nurmala; Tubagus Umar Syarif Hadi Wibowo; Astri Rachmayani (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to obtain an overview of the stress levels of students in facing online learning during the Covid-19 Pandemic. This research method using quantitative descriptive. The data collection method was carried out by distributing questionnaires using a Likert scale. This research was conducted on students majoring in Guidance and Counseling, Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University with a population of 112 people. The data analysis process of this research is quantitative descriptive with the SPSS for windows version 12 program, obtained reliability results of 0.780 analysis of the normality test technique using the Kolmorgrov-Smirnov significant value of 0.424 data with normal distribution. In general, subjects have a moderate stress level (96.4%). Keywords:stress level, online learning, covid-19 pandemic